ANALYSIS OF SOCIO-ECONOMIC, TECHNOLOGICAL, ENVIRONMENTAL CHARACTERISTICS OF THE LIFE CYCLE OF TEXTILE PRODUCTS - PARASKA, OLGA; PODOLINA, КATERYNA; HES, LUBOS; KOVTUN, HRYSTYNA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article analyzes the socio-economic, technological, ecological characteristics of the life cycle of textiles, their impact on the environment and human health. According to the results, the directions of safe manufacture and use of textile products in order to preserve natural resources and human health are proffered.Analysis of socio-economic, technological, ecological characteristics of the life cycle of textile products showed that 45% of textile products can be reused, 30% are suitable for processing into technical textiles, 20% - textile fibers. Only 5% of used textile products are waste that needs to be disposed of. Extending the service life of textiles by 9 months can reduce energy, water and СО2 emissions by up to 30%, which contributes to the preservation of natural resources and human health.Based on the analysis, the following directions of safe manufacture and exploitation of textile products are proffered:- raising awareness of the impact of textile manufacturing on the environment and human health;- regardful use of natural and human resources;- reusing and upcycling of textile products;- recycling of waste materials and products to create new ones;- creation of prerequisites for safe exploitation and cleaning of textile products;- application of technologies of soft cleaning of textile products which reduce expenses of the electricity and natural resources at the same time;- reduction of the use of natural resources and emissions into the environment;- improving ecological and socio-economic indicators throughout the life cycle of textiles.Such recommendations allow manufacturers to improve the environmental safety of production processes, and consumers to buy with more rationality, use less clothing, reducing the generation of textile waste. These, in turn, are important factors that extend the service life of textiles, reduce the ecological impact on the environment and human health.
Keywords: textile products; life cycle of product; textile industry; resource saving; sustainable development